Determination of the rock layers of the earth using the adaptive resonance theory network ART1 - Maha Albadrani (College of Education for Pure Sciences, 2009)
ABSTRACT The focus of the present research is on the issue of specified of the earth rocky geologic layers through the use of a Artificial Neural Network called the Adaptive Resonance Theory Network (ART1). The research discuss the ability of the Artificial Neural Network to specified the stratum rocky geologic to the earth through to enter specifications and characteristic of spring layer, since the network of adaptive Resonance Theory Network (ART1) have property to work style to make similar to human Brain work wherever in keeping the old A knowledge of data when a new information added to any field. The result show the capability the Adaptive Resonance Theory Network (ART1) to make the limitation the earth rocky geologic layers in fast and qualified Technique.